Networking with peers: Evidence from a P2P lending platform - Xiao Chen; Zhaohui Chong; Paolo Giudici; Bihong Huang (Asian Development Bank Institute (ADBI), 2020)
The paper investigates the role of network centrality in predicting borrowers' and lenders' behavior in peer-to-peer (P2P) lending. The empirical analysis of data from Renrendai, a leading lending platform in the People's Republic of China, reveals that the lenders who are at the center of a network not only invest larger amounts but also invest more swiftly than their peers, reflecting the information advantage arising from their position in the network. Furthermore, the borrowers who are at the center of a network are able to borrow at lower interest rates and with higher success rates. At the same time, they are less likely to default. These findings imply that, in the P2P lending market, network linkages not only enhance market efficiency but also encourage reputation protection.
Keywords: C21; C58; E44; G21; 330; network centrality; social networks; peer-to-peer lending; lending behavior; loan outcomes